The detection of Edwardsiella tarda by aptamer-based qPCR - Bai, Yue; Li, Xuefei; Yan, Wei; Zhao, Lingmin; Huang, Lixing; Yan, Qingpi; Wang, Jiaen; Weng, Qibiao; Zheng, Jiang (Frontiers in Veterinary Science, 2025)
The Edwardsiella tarda bacterium can infect a wide variety of fish species and is a common pathogen in aquaculture. Rapid and accurate detection of the pathogen is the premise and basis for its disease prevention and control. In this study, an aptamer with high affinity and specificity was used to bind E. tarda. The aptamers that bound to the pathogen were then separated and used as the templates for SYBR Green I real-time quantitative polymerase chain reaction (qPCR) amplification. The Ct values obtained by qPCR can be used to quantitatively analyze the concentration of E. tarda, thereby establishing an aptamer-qPCR method for the quantitative detection of the pathogen with good specificity. Results showed that the Ct value of E. tarda was significantly lower than that of non-target bacteria (Pseudomonas plecoglossicida, Pseudomonas aeruginosa, Escherichia coli, Vibrio anguillarum, Vibrio alginolyticus, Vibrio harveyi and Aeromonas hydrophila) (p < 0.01). It had a good quantitative detection effect and showed good linearity in the range of 1–109 CFU/mL. This method also had high sensitivity and stability, with minimum detection limit reaching 1 CFU/mL. This method was used to detect E. tarda in spiked water and tissue samples, proving its applicability for the detection of E. tarda in aquatic products, foods, and in the aquatic environment.